Versatile Nasal Application of Cyclodextrins: Excipients and/or Actives? - Giovanna Rassu; Milena Sorrenti; Laura Catenacci; Barbara Pavan; Luca Ferraro; Elisabetta Gavini; Maria Cristina Bonferoni; Paolo Giunchedi; Alessandro Dalpiaz (MDPI AG, 2021)
Cyclodextrins (CDs) are oligosaccharides widely used in the pharmaceutical field. In this review, a detailed examination of the literature of the last two decades has been made to understand the role of CDs in nasal drug delivery systems. In nasal formulations, CDs are used as pharmaceutical excipients, as solubilizers and absorption promoters, and as active ingredients due to their several biological activities (antiviral, antiparasitic, anti-atherosclerotic, and neuroprotective). The use of CDs in nasal formulations allowed obtaining versatile drug delivery systems intended for local and systemic effects, as well as for nose-to-brain transport of drugs. In vitro and in vivo models currently employed are suitable to analyze the effects of CDs in nasal formulations. Therefore, CDs are versatile pharmaceutical materials, and due to the continual synthesis of new CDs derivatives, the research on the new nasal applications is an interesting field evolving in the coming years, to which Italian research will still contribute.